THE PHYSICAL CONDITIONS OF THE CENTRAL PART OF ORION A HII REGION BY THE RADIO RECOMBINATION LINES AT 8 AND 13 MM - Tsivilev, A. P.; Parfenov, S. Yu.; Krasnov, V. V. (Одеські астрономічні публікації, 2016)
Observations of recombination radio lines (RRL) of hydrogen, helium (H, He) and carbon (C) were carried out in several positions of the HII region Orion A with RT22 radio telescope (Pushchino, Russia) at the wavelengths of 8 and 13 mm. The information about the ionization structure of the HII region was received. It is obtained that the measured helium abundance increases in the directions to "North" and "West” with a maximum at angular distances of 100-150˝ after which it declines. The maximum measured relative helium abundance, y+ = n(He+)/n(H+), is in the range of 9.4 – 11.0 %, therefore the actual He abundance n(He)/n(H)) is ≥ 9.4(±0.5) %. With these estimates, the lower limit of the primordial helium abundance Yp ≥ 25.19 (±1.15) % should be expected. This limit is still not strong enough to assert the excess over Yp predicted by the standard cosmological model (≈ 24.8%), but it admits the existence of unknown light particles. The y+ behavior and model calculations indicate that Teff (effectivetemperature) of q1 Ori C star is 35000 – 37500 K, corresponding to the star spectral type of ≈ O6.5 V, which is important for the calibration of hot OB-stars. Measured electron temperatures (Te) of the HII region, taking into account the deviations from the LTE, are in the range of 6600 – 8400 K and are strictly decreasing in direction to the “East”. Alas information on the turbulent velocities of the ionized gas and its electron density was obtained.